Production of extruded snacks by utilization of watermelon (Citrullus vulgaris) seed flour - Raja, M Praveen; Karthiayani, A; Selvan, P; Nithyalakshmi, V (Journal of Postharvest Technology, 2019)
Watermelon (Citrullus vulgaris) seed is one of the under-utilized oil seed which has good nutritional value like protein, minerals and unsaturated fatty acids. The extruded snacks were prepared by incorporation of watermelon seed flour in rice-corn flour blend. The dehulled watermelon seed was milled into flour and incorporated into rice-corn blend at 10, 15 and 20% proportions for the preparation of extruded snacks. The optimal level of incorporation of watermelon seed flour (WSF) in extruded snacks was found to be 15% (w/w) based on evaluation of physical and sensory characteristics of the extrudates. The extruded snacks prepared using this optimal formulation was packed by nitrogen flushing and studied for properties such as proximate composition peroxide value, hardness, colour (L*, a*and b*) and sensory characteristics during 90 days of storage and compared with control extruded snacks based on rice-corn flour blend. As a result, the WSF incorporated extruded snacks was found to remain in good condition till the end of storage period.